Functional and taxonomic diversities are better early indicators of eutrophication than composition of freshwater phytoplankton - Machado, Karine Borges; Bini, Luis Mauricio; Melo, Adriano Sanches; Andrade, Ariany Tavares de; Almeida, Marcela Fernandes de; Carvalho, Priscilla; Teresa, Fabrício Barreto; Roque, Fábio de Oliveira; Bortolini, Jascieli Carla; Padial, Andre Andrian; Vieira, Ludgero Cardoso Galli; Dala-Corte, Renato Bolson; et al. (Springer Nature, 2022)
Eutrophication is a key threat to aquatic biodiversity around the world, but especially in the Cerrado biome that has undergone intensive land use conversion and fertilizer use. In this study, we investigated how water conditions and different taxonomic and functional indicators of phytoplankton communities responded to eutrophication over time and also identified which of these variables can act as early indicators of eutrophication. We used a mesocosm experiment to simulate shallow lakes and added nutrients to produce eutrophic and oligo-mesotrophic environments. We found that conductivity and turbidity increased with the nutrient enrichment process. Eutrophication did not change species richness; however, it increased the total phytoplankton density and chlorophyll-a concentration and decreased the diversity indices (Shannon–Wiener diversity and Pielou’s equitability) over time, for both taxonomic and functional facets. Our results indicate that eutrophication may not have marked effects on the composition of the initially dominant organisms in the short term but does increase the density of certain organisms and exclude rare species and functional groups in eutrophic environments along the time. Furthermore, the diversity indices are more sensitive indicators of eutrophication compared to abiotic indicators and composition of species and functional groups. Therefore, they may be considered reliable early warnings of ecosystem changes.
Keywords: Algae; Freshwater mesocosms; Functional groups; Global change; Nutrient enrichment